Diffusion Decay Coefficient for Chloride Ions of Concrete Containing Mineral Admixtures - Jae-Im Park; Kwang-Myong Lee; Soon-Oh Kwon; Su-Ho Bae; Sang-Hwa Jung; Sung-Won Yoo (Advances in Materials Science and Engineering)
The diffusion coefficient for chloride ions and the diffusion decay coefficient for chloride ions are essential variables for a service life evaluation of concrete structures. They are influenced by water-binder ratio, exposure condition, curing temperature, cement type, and the type and use of mineral admixture. Mineral admixtures such as ground granulated blast furnace slag, fly ash, and silica fume have been increasingly used to improve resistance against chloride ions penetration in concrete structures built in an offshore environment. However, there is not enough measured data to identify the statistical properties of diffusion decay coefficient for chloride ions in concrete using mineral admixtures. This paper is aimed at evaluating the diffusion decay coefficient for chloride ions of concrete using ordinary Portland cement or blended cement. NT BUILD 492 method, an electrophoresis experiment, was used to measure the diffusion coefficient for chloride ions with ages. It was revealed from the test results that the diffusion decay coefficient for chloride ions was significantly influenced by W/B and the replacement ratio of mineral admixtures.